Measuring the Milky Way in M-dwarfs - van Vledder, Isabel; van der Vlugt, Dieuwertje (Student Undergraduate Research E-journal!, 2015)
We report 274 M-dwarfs found in the Brightest of Reionizing Galaxies (BoRG) survey for high redshift galaxies. Using these, we fitted a model for the disk and halo with a fixed scale length at h = 2.6 kpc. We found a scale height z0 of 0.60±0.03 kpc, flattening parameter κ of 0.45±0.04 and a powerlaw-index p of 2.4±0.07. For the total number of M-dwarfs in the disk and halo we found 26.7_(-6.2)^(+9.3)×10^9. The upper limit for the halo fraction of M-dwarfs in the halo is 7_(-4)^(+5) %. The total mass upper limit was determined to be 1.99_(-0.5)^(+0.73)×10^9 Solar masses.